2021
DOI: 10.1017/s1368980021001397
|View full text |Cite
|
Sign up to set email alerts
|

Developing an online food composition database for an Indigenous population in south-western Uganda

Abstract: Objective: To develop an online food composition database of locally consumed foods among an Indigenous population in south-western Uganda. Design: Using a community-based approach and collaboration with local nutritionists, we collected a list of foods for inclusion in the database through focus group discussions, an individual dietary survey and markets and shops assessment. The food database was then created using seven steps: identification of foods for inclusion in the database; ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Among them, eleven (B (46) , D (49) , H (53) , I (54) , J (55) , K (31) , L (56) , N, O (58) , Q (60) and R (61) ) were developed in Europe, five (A (45) , F (51) , G (52) , M (70) and P (59) ) in North America (USA and Canada), one (E (50,64) ) in Australia and one (C (48) ) in South Korea. Five (A (71) , I (72) , J (36) , K (73) and R (61) ) have already been adapted to be used in another country, and in particular, two (I (72) and J (74) ) have already been adapted for low-income countries (Middle East countries, Peru or the South-Asia region). Only one language is available in twelve tools (C-H, K, L-O and Q) (among them six in English: E-H, M and O), while the other six tools (C, D, K, L, N and Q) are in various languages.…”
Section: General Descriptionmentioning
confidence: 99%
“…Among them, eleven (B (46) , D (49) , H (53) , I (54) , J (55) , K (31) , L (56) , N, O (58) , Q (60) and R (61) ) were developed in Europe, five (A (45) , F (51) , G (52) , M (70) and P (59) ) in North America (USA and Canada), one (E (50,64) ) in Australia and one (C (48) ) in South Korea. Five (A (71) , I (72) , J (36) , K (73) and R (61) ) have already been adapted to be used in another country, and in particular, two (I (72) and J (74) ) have already been adapted for low-income countries (Middle East countries, Peru or the South-Asia region). Only one language is available in twelve tools (C-H, K, L-O and Q) (among them six in English: E-H, M and O), while the other six tools (C, D, K, L, N and Q) are in various languages.…”
Section: General Descriptionmentioning
confidence: 99%
“…The Batwa and Bakiga are aware of the consequences that unavailability of food can have on maternal and child health. A study conducted in 2019 showed that the diet of Batwa and Bakiga communities is low in proteins and fats, and the caloric content of the most commonly consumed foods is low or very low, with negative implications for child nutrition [28]. For these reasons, women highlighted the need for the District and Government to improve access to, and security and ownership of, more land to cultivate, and distribution of food to pregnant and lactating mothers and children.…”
Section: Discussionmentioning
confidence: 99%
“…They work mostly as farmers, hired by the Bakiga; some are craft makers or brick makers or work in tourism [18]. However, the absence of a traditional culture of farming and low socio-economic status exacerbate food insecurity [27] which have an impact on individual nutrition, and can affect negatively child health [28]. Although many Batwa and Bakiga families are poor, Batwa per capita income is substantially lower than the national average (0.36 US dollars/day compared to 0.99 US dollars/day) [24].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In addition, we described how food was cooked, processed and stored. The second stage involves development of an automated online food database [22] for south-western Uganda, and results are reported in Scarpa et al [13]. To create the food list, we used a mixed-method research design with field-based data collection, including focus group discussions, individual dietary surveys and market and shop visits.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion of adjacent Indigenous and non-Indigenous communities allowed us to explore the extent to which cultural constructs of food systems might influence the development of food lists and nutritional assessment methods at the local level. We, therefore, formulated the following objectives: (1) to identify the range of foods and dishes consumed by households (with nutrient composition details in the manuscript of Scarpa et al [13]);…”
Section: Introductionmentioning
confidence: 99%